Problems and Their Solutions in Genetic Counseling Education in Japan - Kohzaki, Hidetsugu (Frontiers in Public Health, 2014)
With the expansion of novel chromosome testing, a career as a certified genetic counselor has been gathering a lot of attention. However, few people certified as a genetic counselor after completing postgraduate courses are able to find employment as a genetic counselor, and their salaries are quite low. It is also questionable whether or not such newly graduated genetic counselors, who have limited life experience and knowledge, can fully understand family issues and properly perform counseling sessions. To address these issues, a wide range of education and training may be necessary. In this study, we examined current problems in genetic counseling education in Japan, and proposed effective measures to address these problems. Toward creating a new society, we are currently establishing a national qualification system and cultivating qualified professionals capable of providing patients with accurate information on chromosome and genetic testing. In addition, these professionals could encourage younger generations to have an interest in genetic counseling. I also hope that these professionals will work not only in Japan but all over the world.